Overview of Family Education and Culture: Masculinity Male Dancer - Fatia Rizky Prawitha; Rahmawati Rahmawati; Baricza Maulid Pradipta (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Gender is a characteristic difference between women and men that are formed from the culture learned and socialized since childhood. Gender characteristics give rise to the notion that men must be masculine, and women must be feminine. The existence of stereotypes about gender roles culturally causes someone who has a profession that is opposite to gender to be considered inappropriate. For example, male dancers are considered not masculine because of society's views. This study wants to describe how male dancers maintain their identity as male and masculine by social perception, the type of masculinity of each subject, and the reasons for respondents choosing the profession of being a dancer. The research method used was a qualitative study in the form of interviews and observations of 3 male respondents who work as towing workers. The theory is used based on Tuncay stating that masculinity can be defined socially as a way to become a man who is defeated into 11 elements. The type of masculinity uses four configurations of masculinity in the masculinity hierarchy and a special learning theory approach in career selection by Krumboltz. From research results known that all respondents still show their masculinity without being influenced by the profession they choose. For respondents to be attractive is what they like. It can be interpreted that one's prophesied does not always affect one's level of masculinity or femininity. Therefore, in the concept of family education, introduction to the profession does not only contain achievement in education but also includes the socialization of values for the development of both self-concept and personality. The importance of family education in the introduction about gender identities and roles in children is a way not to be affected by the stereotypes of gender roles that apply in society but to see the needs of children in self-development and personality.